On Being Able to Walk Twenty Metres: The Introduction of Personal Independence Payments. (18th August 2019) - Alldridge, Peter
Abstract : The Welfare Reform Act 2012 introduced Personal Independence Payments (PIPs), and in particular the enhanced‐rate mobility component (ERMC), with its twenty‐metre test to replace the more flexible fifty‐metre test for the higher‐rate mobility component of Disability Living Allowance (DLA). The government objective was to reduce the number of recipients of the benefits, which carry eligibility to the Motability scheme. Rather than modify DLA so as to cure its perceived faults, the government decided to ignore the past and start afresh. The article examines the implementation of PIP, including the treatment of the application of the author, and shows that the norms according to which DWP operates the benefit, are radically at variance with those in the Social Security (Personal Independence Payment) Regulations 2013. These developments have been central to the creation of a 'hostile environment' for people with disabilities.